Primary school English-language education in Asia : from policy to practice - Annual Conference of Asia TEFL (2010 : Hanoi, Vietnam); Spolsky, Bernard; Moon, Young-in. (New York : Routledge, 2012)
"In Asia, English is no longer a foreign language but a key resource for education, government, business and the general public. Whereas thirty years ago, British and American experts believed that the best way to improve the quality of English teaching was to cancel any programs below the secondary level, Asian nations as well as European are now introducing English in primary school. But there are major obstacles to overcome: the training of enough local teachers or the hiring of English speakers, the preparation of suitable teaching materials, the development of useful tests, and the design of workable curriculums. The chapters in this book, written by leading English-teaching professionals in seven Asian countries and originally delivered at the 2010 Annual Conference of Asia TEFL which took place in Hanoi, Vietnam, describe and analyze national policies and how they are implemented. The coverage is wide: China with its huge number of students learning English, Japan working to make the transition from elementary to secondary school seamless, Singapore continuing to use English as medium of instruction for its multilingual population, Korea developing English education policies to recognize the increased role of English alongside the national language, India building on its colonial past to make English an economic resource, Vietnam fitting English into a program of national rebuilding, and Taiwan spreading its English teaching outside the national capital. This is not a report of the views of outside experts, but of local experiences understood by local scholars of international standing. Policy makers, educators, researchers and scholars will be able to gain valuable insights from Asian experts"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: English language -- Study and teaching (Elementary) -- Asia -- Congresses; Education and state -- Asia -- Congresses; Electronic books